Survey of the Service Offer of Fitness Clubs for Group Classes in Debrecen - Pfau, Christa; Bartha, Éva; Bácsné Bába , Éva; Szabóné Szőke, Réka; Müller, Anetta (International Journal of Engineering and Management Sciences, 2021)
The economic and social importance of the fitness sector is steadily increasing. The range of services provided by fitness centers is expanding and the popularity of fitness clubs is constantly growing. Fitness workouts are easily accessible for everyone, and there are numerous types of fitness centers which can play an important role in everyday physical activity. There are many factors that can influence the choice of fitness consumers for the gym, also fitness professionals play a key role in this regard. It is essential for fitness clubs in order to remain competitive on the market, to employ fitness instructors with the optimal personality and expertise, but in many cases, there is a lack of verification of qualifications. In our study, we conducted interviews with 20 fitness instructors who work in a fitness center that offers group lessons to consumers. The questionnaire included questions about consumer preferences, fitness facilities, trainers qualifications, and activities. Our study was made among eleven fitness clubs in Debrecen. The number of fitness clubs is constantly changing, with each year closing, opening or rebuilding fitness centers, which vary widely in size and number of services offered. The majority of respondent trainers are women as are the participants women in group lessons. Most of the interviewed trainers have OKJ qualifications, but the results reflect that fitness providers have not checked their qualifications at all before applying them. Fitness professionals play an extremely important role in leisure sports, contributing in maintainance and development of the fitness consumers’s health. Their work has a particular responsibility, as they can influence the physical and mental health of others in both positive and negative ways. Not only to avoid the risk of injuries, but also to prevent long-term health damage, fitness professionals play an important role. Controlling the qualifications also be in the interest of fitness clubs, not only avoiding accidents, but also increasing attendance at group classes by employing reliable, excellent personal trainers.